PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN GUNUNG SINDUR KABUPATEN BOGOR - Fahru Roji Malik; Theobaldus Boro Tura (Journal of Research and Publication Innovation, 2025)
Work discipline on employee performance at the Gunung Sindur District Office, Bogor Regency, both partially and simultaneously. The research method employed is quantitative and associative. The population consists of all employees at the Gunung Sindur District Office, Bogor Regency, with a sample size of 62 respondents selected using a saturated sampling technique. The type of data used is quantitative, collected through primary and secondary sources, including observation, interviews, questionnaires, literature reviews, and documentation. The data analysis techniques include instrument testing, classical assumption testing, multiple linear regression analysis, correlation and determination coefficient testing, and hypothesis testing using t-tests and F-tests. The partial results of the study reveal that leadership style significantly affects employee performance at the Gunung Sindur District Office, Bogor Regency, with a calculated t-value of 2.514, exceeding the t-table value of 2.001, and a significance value of 0.015, which is less than 0.05. Similarly, work discipline significantly affects employee performance, with a calculated t-value of 6.375, exceeding the t-table value of 2.001, and a significance value of 0.000, which is also less than 0.05. Simultaneously, it was found that leadership style and work discipline have a significant influence on employee performance, with an F-value of 105.574, exceeding the F-table value of 3.15, and a significance value of 0.000, which is less than 0.05. The determination level is 78.2%, while the remaining 21.8% is influenced by other factors not included in this study